Being Human in a Buddhist World An Intellectual History of Medicine in Early Modern Tibet. - Gyatso, Janet (New York : Columbia University Press, 2015)
Critically exploring scientific thought and its relation to religion in traditional Tibetan medicine, Being Human expands our sense of Tibetan cultural history, unpacking the intersection of early modern sensibilities and religious ideals during the time of the Fifth Dalai Lama. Studying the adaptation of Buddhist concepts and values to medical concerns, the book also advances an appreciation of Buddhism's role in the development of Asian and global civilization. Through its unique focus and sophisticated reading of source materials, Being Human captures the religious character of medicine in.
7. The Ethics of Being Human: The Doctor's Formation in a Material RealmConclusion: Ways and Means for Medicine; Notes; Bibliographies; Index
Description based upon print version of record.
Keywords: Buddhism--Tibet Region--History.; Medicine, Tibetan--History.; Medicine--Religious aspects--Buddhism.; Buddhism -- Tibet Region -- History; Medicine, Tibetan -- History; Medicine -- Religious aspects -- Buddhism; RELIGION / Comparative Religion; Electronic books